Rehabilitation Interventions to Promote Recovery from Schizophrenia: A Systematic Review - Morin, Laurent; Franck, Nicolas (Frontiers in Psychiatry, 2017)
Only one out of seven patients recovers after a first episode of psychosis despite psychiatric care. Rehabilitation interventions have been developed to improve functional outcomes and to promote recovery. We conducted a systematic review of the effectiveness of the main psychiatric rehabilitation interventions following a search of the electronic databases Pubmed, ScienceDirect and Google Scholar using combinations of terms relating to cognitive remediation, psychoeducation, cognitive-behavioral therapies and schizophrenia. Eighty articles relevant to the topic of interest were found. According to results, cognitive remediation has been found to be effective in reducing the impact of cognitive impairment, social skills in the learning a variety of skills and to a lesser extent in reducing negative symptoms, psychoeducation in improving compliance and reducing relapses, and cognitive therapy in reducing the intensity of or distress related to positive symptoms. All psychosocial rehabilitation interventions should be considered as evidence-based practices for schizophrenia and need to become a major part of the standard treatment of the disease.